Challenges in management of tuberculosis under programmatic conditions: Perceptions of health care providers from four states of India - Babu, Ranjith; Kathirvel, Soundappan; Anand, Tanu; Chadha, Sarabjit (Indian Journal of Community Health, 2017)
Background: Among the global estimation of 10.4 million new cases of Tuberculosis (TB) in 2015, 27% of cases are contributed by India. Revised national TB control program (RNTCP) started in 1993, and now heading towards for universal access. Despite its achievements, the program faces number of implementation challenges. This qualitative study explored ‘what is healthcare providers take on it?’. Material & Methods: A total of 28 in-depth interviews were conducted in Uttarakhand, Chhattisgarh, Delhi and Maharashtra from October 2014 to January 2015, under the thematic areas of finance, human resource, and communications. Participants included senior level policy makers like principal secretaries of health, National Health Mission Directors, Director Health Services, state TB officers and district TB officers, medical officers, community volunteers and TB consultants from international agencies. Analytic induction method was used for data analysis. Results: Participants identified many barriers in the overall management and implementation of RNTCP. Convergence of RNTCP needs to be more effective. Inadequate Human resources, issues in public private partnership, insufficient budget allocation and interrupted fund flow, inefficient Information Education and Communication strategy are a few. Conclusion: This study could gather the perspectives of senior health officials, implementers and other stakeholders on challenges in implementation of TB control programme in four states. Challenges perceived by them are vital in strategic revisions of RNTCP.